Analisis Praktikalitas Media Pembelajaran Interaktif Berbasis Swishmax Dalam Materi Hukum Newton Dan Penerapannya Kelas VIII SMP - Ratna Indriasari; Andi Muh Akbar Saputra; Enny Zarvianti (Journal on Education, 2023)
In the era of technology and information that continues to develop, the use of interactive learning media is an important focus in education. However, in-depth research is still needed to test the effectiveness of SwishMax-based interactive learning media in improving student learning outcomes. This study aims to analyze the effectiveness of SwishMax-based interactive learning media on Newton's law material and its application in class VIII SMP. The method used in this research is 4D (Define, Design, Develop, Disseminate) in the development of learning media. This research trial involved students and teachers to collect data on the practicality of the developed learning media. The results showed that SwishMax-based interactive learning media was very practical for students to use in learning with a practicality percentage of 89.37%. In addition, this learning media was also found to be very practical when used in other classes. In conclusion, interactive learning media based on SwishMax on Newton's Laws and Their Applications in class VIII of junior high school meets the criteria of being very practical and effective.